Comportamiento de las alteraciones citológicas y algunos factores asociados en mujeres atendidas en una IPS Pública del Suroeste Antioqueño, julio-2014 a julio-2015 (2015)
ABSTRACT: In Colombia, cervical cancer is the main cause of death in women. Even though the mortality rate has decreased over the last decade, it is still a public health problem in the country and the region. Methods: a descriptive study was carried out with 3544 women who consulted the cytology service at a public health institution (IPS) in Andes – Antioquia, Colombia, between July 2014 and July 2015. Results: the distribution of the cytological results showed that 4.2 % had a cytological alteration. The report on atypical squamous cells of undetermined significance (ASC-US) was the most prevalent with 2.3 %, followed by low-grade squamous intraepithelial lesions (LSIL) with 1.3%, high-grade squamous intraepithelial lesions (HSIL) with 0.3 %, and atypical squamous cells which do not exclude high-grade squamous intraepithelial lesions (ASC-H) with 0.2 %. ASC-US and low-grade LSIL were more prevalent in women between 21 to 40 years of age. Regarding the number of children, women who had their first sexual intercourse before 18 years of age presented the highest percentage of cytological abnormalities. In the distribution of lesions, it was found that ASCUS and LSIL were more common in women who had given birth between zero and three times than in those who had gone through childbirth more than four times. ASC-H and HSIL presented a similar behavior in both groups. Conclusions: in general, the prevalence of alterations in all groups evaluated in this study was low in comparison with previous similar studies.